Fabrication, structure and dielectric properties of multilayer heterostructures based on Ba2NdFeNb4O15 and Sr0.6Ba0.4Nb2O6 thin films grown on SrRuO3(001)/MgO(001) - D. V. Stryukov; Ya. Yu. Matyash; V. A. Bobylev; A. V. Nazarenko; A. V. Pavlenko (Journal of Advanced Dielectrics)
By X-ray diffraction and dielectric spectroscopy, the crystal structure, phase composition, and properties of Sr[Formula: see text]Ba[Formula: see text]Nb2O6/Ba2NdFeNb4O[Formula: see text]/Sr[Formula: see text]Ba[Formula: see text]Nb2O6/Ba2NdFeNb4O[Formula: see text]/SrRuO3/MgO and Ba2NdFeNb4O[Formula: see text]/Sr[Formula: see text]Ba[Formula: see text]Nb2O6/Ba2NdFeNb4O[Formula: see text]/Sr[Formula: see text]Ba[Formula: see text]Nb2O6/SrRuO3/MgO multilayer heterostructures were studied. The heterostructures were manufactured under identical conditions but differing in the layer deposition sequence. It is shown that the orientation domains are formed in each Ba2NdFeNb4O[Formula: see text] (BNFN) and Sr[Formula: see text]Ba[Formula: see text]Nb2O6 (SBN) layers. BNFN and SBN layers have tetragonal unit cells with tensile out-of-plane strain and compression in-plane strain. At [Formula: see text]C both heterostructures are characterized by fairly high relative permittivity values. The reasons for the revealed regularities are discussed.